The Mediating Role of Trust in E-commerce Purchase Intention: Evidence from Lazada Users in Jakarta - Selvi Kurumbatu (Asian Journal of Social and Humanities, 2024)
This study aims to analyze the influence of perceived service quality, perceived reputation, and social presence on purchase intention, with trust as a mediating variable, on Lazada users in DKI Jakarta. Purchase intention is a consumer's intention to make a purchase that is influenced by various factors, including perceived service quality, perceived reputation, and social presence on an e-commerce platform. Consumer trust is an important key in mediating the relationship between these variables and purchase intention. This study uses a quantitative method with data collection through questionnaires distributed to Lazada users in DKI Jakarta. Data analysis was carried out using multiple regression models and path analysis to evaluate the role of trust in mediating the relationship between independent variables and purchase intention. The results of the study indicate that perceived service quality, perceived reputation, and social presence significantly influence purchase intention through trust. Consumer trust is proven to be an important mediator, which strengthens the influence of the three independent variables on purchase intention. These findings provide implications for e-commerce platform managers in improving service quality, building a good reputation, and strengthening social presence to increase consumer trust and purchase intention.